Dyskeratosis Congenita: A Case Report - Sumi, Shahnaz Pervin; Mamun, Mohammad Abdullah Al; Islam, Mirza Md Ziaul; Alam, Md Jahangir (Bangladesh Journal of Child Health, 2023)
Dyskeratosis Congenita (DC) is a rare inherited bone marrow failure disorder characterized by lacy reticulated skin pigmentation, nail dystrophy and mucosal leukoplakia. In DC bone marrow failure is the main cause of premature death with an additional predisposition to malignancy. DC results from progressive shortening of telomeres resulting in DNA replication. X-linked recessive is the main mode of inheritance. Most of the patients respond to Androgen therapy. This is a case report of a 5-year-old boy presented with features of bone marrow failure and had abnormality of skin, oral mucosa and nail. His complete blood count with peripheral blood film showed pancytopenia and no blast cell. Hypocellular marrow was present in his Bone marrow examination. Chromosomal analysis- fluorescence in situ hybridization (FISH) revealed very short telomere of chromosome. Microarray genotyping showed DKC1 gene abnormality. BANGLADESH J CHILD HEALTH 2022; VOL 46 (1) : 39-41